Community Connections: Employee Volunteering: FCS9235/FY777, 12/2005 - Lesmeister, Marilyn K.; Romero, Anne (EDIS, 2005)
Whether it is a small, local business, or large, national corporation, employees can be a source of volunteer power in any community. Employees can participate in a wide range of volunteer activities and programs that are supported by their employers. Employee volunteers are often equipped with specialized skills, information, and a fresh perspective to help address community issues and challenges (Lautenschlager, 1993). There can be benefits to the individual employee, the employer, the corporation, and the community. This document is FCS9235, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2005.